Metal-bearing nanomaterials for oral antibacteria: Mechanisms and applications - Ke Quan; Yuqing Zeng; Sijia Gao; Yanli Lei; Le Yang; Yibo Zhou; Lucky Poh Wah Goh; Zhihe Qing (Elsevier, 2025)
The prevalent oral diseases, such as dental caries, chronic gingivitis, and periodontitis, which are primarily caused by pathogenic bacteria, pose significant public health risks and impose substantial economic burdens. However, conventional treatment strategies for oral pathogens rely on mechanical debridement and antibiotic treatment, which remain unsatisfactory and contribute to the emergence of antimicrobial resistance pathogens. The escalating crisis of antibiotic resistance and the intricate microbial communities in oral niches urgently demand innovative antimicrobial strategies that can overcome these issues. Metal-bearing nanomaterials (MBNs), as an integration of metallic components with other substances such as polymers or inorganic materials, have demonstrated improved antimicrobial effectiveness while mitigating the toxicity associated with pure metals in oral environments. This review provides an innovative overview of designing and utilizing MBNs for oral antimicrobial applications, bridging the gap between nanomaterial design and clinical dentistry needs while guiding the development of next-generation antimicrobials in the post-antibiotic era. Firstly, we categorize and elucidate the main antibacterial mechanisms of metallic components in MBNs. Furthermore, a comprehensive summary is provided on the up-to-date advancements in using MBNs for oral antibacterial purposes, highlighting the pivotal role of metals in enhancing antibacterial properties. Finally, we discuss the existing challenges and potential future developments to establish a theoretical foundation for ongoing progress and clinical approval.